PEMBINAAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM LISA (LIHAT SAMPAH AMBIL) DI SMPN 10 MATARA - Rahmi, Lalu Sumardi, Muh. Zubair (FKIP UMN ALWASHLIYAH, 2026)
The increasingly concerning waste problem requires solutions not only technically, but through behavioral changes and the development of environmentally conscious community characters. This study aims to describe the implementation, impacts, and supporting and inhibiting factors of the LISA Movement (See Trash Pick Up) in developing environmentally conscious characters at SMPN 10 Mataram. This study uses a qualitative approach with a case study type. Data were collected through semi-structured interviews, passive participant observation, and documentation. Data validity was tested by triangulation of sources, techniques, and time. Data analysis followed the Miles, Huberman, and Saldana model which includes data condensation, data presentation, and conclusions. The results of the study indicate that: (1) The implementation of the LISA Movement is structured through routine morning activities, breaks, and after school with a unique mechanism of